Creating Interactive Videos for Teaching and Learning - Sarah Flora, Samson Juan; Tan, Ping Ping (Centre for Applied Learning and Multimedia, 2020)
Due to the COVID-19 pandemic outbreak, Malaysia began its lockdown on 18 March 2020, after our Prime Minister Yang Amat Berhormat Tan Sri Dato’ Haji Muhyiddin bin Haji Mohd Yassin officially announced the Movement Control Order (MCO) two days prior. At such short notice, UNIMAS took the drastic decision to embrace fully online teaching and learning (T&L) for all courses. We had to revamp our teaching and learning strategy with the most notable shift; recorded lecture videos. In a physical lecture, we can directly engage with students, however, with videos, such interaction is lost. How do we know if the students are actually paying attention or, do they understand what is presented in the video? In this article, we share our experience in using one of the hidden gems in eLEAP that is very useful for creating interactive videos. At the end of the article, we provide six simple steps that can be used as a guide.